Large overjet as a risk factor of traumatic dental injuries: a prospective longitudinal study - Jean-Paul Schatz; Enrico Ostini; Magnus Hakeberg; Stavros Kiliaridis (SpringerOpen, 2020)
Abstract Purpose The aim of this longitudinal prospective study was to evaluate if schoolchildren with large overjet experience a greater risk of traumatic dental injuries (TDI) compared to children with normal or small overjet. Methods A sample of children aged 6‑13 years was prospectively evaluated after 1 year: from the initial sample, data concerning trauma cases of 1413 children were collected to determine the number and types of injuries, the influence of overjet on the risk of TDI, and the relationships between trauma, age, and gender. Results The observed prevalence of trauma was higher for boys, with the largest frequency between the ages of 8 to 12 years: 67.9% of all injuries were hard tissue injuries and 32.1% subluxation and luxation injuries. Children with an overjet of 6 mm or more showed a statistically increased risk of getting trauma [RR = 3.37 with CI (1.81; 6.27)]. Conclusion In this prospective study, overjet stood out among variables as the most significant risk factor of TDI: an increased overjet of 6 mm or more had a major impact on the risk of trauma, which would speak in favor of early orthodontic correction of an increased overjet to reduce the prevalence of dental trauma